HYPERTENSION, CLASSIFICATION AND PATHOGENESIS - Ergashov Bekhruzjon Komilovich; Axmedov Shamshod Jamshidovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation Information about hypertension, its classification, mechanisms of development, elements of non-drug treatment and methods of preventing the disease are provided.